Instant payments as a new normal: Case study of liquidity impacts for the Finnish market - Matti Hellqvist; Kasperi Korpinen (Bank of Finland, 2021)
The amount of central bank money, or liquidity, needed to settle payments, depends on the way the settlement is organized. It is largest when payments are settled individually on gross basis and smallest with settlement in one big netting cycle. Retail payments are increasingly processed in instant payment schemes and systems. We evaluate how the result of this transition affects the liquidity needs of the Finnish banks. For the analysis we generate artificial transaction level data, which mimics the Finnish retail payment flows processed in the STEP2 system. This allows us to estimate the difference between the liquidity needs for the settlement in a cycle based model and in a full instant payment mode. We also present a regression model for the bank level additional liquidity needs. A full migration to instant payments is expected to cause only a small aggregate increase in the liquidity needs. However, the variations between banks or between days can be significant and emphasize the need of liquidity buffers.
urn:nbn:fi:bof-202110122055
Keywords: 330; instant payments; liquidity needs; payment systems; netting